Learning from an Electronic Chart Testbed - Eaton, R. M.; Astle, H.; Glavin, S. J.; Grant, S. T.; Masry, S. E.; Shaw, B. W. (The International Hydrographic Review, 2015)
Over the past five years, the Canadian Hydrographic Service’s Electronic Chart Testbed has provided insights into the way an electronic chart (EC) will handle chart data — and from this the appropriate form for the Hydrographic Office to provide and electronic chart database; it has stimulated suggestions about how the display should be designed; it has provided a practical model for use in planning IHO specifications — and followed on to test these by implementing them; and it has shared in giving mariners demonstrations of some of the eventual capabilities of ECDIS, so that they can start thinking about what they need from it. This paper describes planning the Testbed; lessons from early tests; initial ideas on electronic chart data and on display design; and the reactions from mariners who saw the Testbed among six electronic charts on board the Norwegian ship LANCE during the 1988 North Sea Project.